A review of straightforward distributed behaviors in swarm robotics - Andrade, Emerson Martins De; Junior, Joel Sena Sales; Fernandes, Antonio Carlos (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This article presents a review of research on swarm behaviors that fall under the categories of behavior-based, physics-based, and rule-based approaches. The authors classify these approaches as straightforward distributed behaviors and argue that despite their differences, they share a common root and can be studied together. The article highlights the diverse range of applications that have been explored using these approaches, such as manipulators, mobile robots, flocks, and escape panic scenarios. The authors aim to provide a shared nomenclature standardization for these behaviors, allowing for better understanding and connection between the different models. This review contributes to the evolution of swarm intelligence research and offers insights into the potential of straightforward behaviors in various domains.